Acid-Base Parameters for Predicting Magnetic Resonance Imaging Measures of Neurologic Outcome after Perinatal Hypoxia-Ischemia: Is the Strong Ion Gap Superior to Base Excess and Lactate? - Mann, Christian; Latal, Beatrice; Padden, Beth; Scheer, Ianina; Goebel, Georg; Bernet, Vera (American Journal of Perinatology, 2012)
We conducted this study to compare the strong ion gap (SIG) with base excess (BE) and lactate for predicting neurologic outcome measured by magnetic resonance imaging (MRI) in newborns with hypoxic-ischemic encephalopathy (HIE). In a retrospective cohort of 39 newborns with HIE treated with whole-body surface cooling (n = 17) and no cooling (n = 22), we measured blood SIG, BE, and lactate at 4, 24, and 48 hours after birth, and determined cerebral injury severity by T1-, T2-, and diffusion-weighted MRI scores at age 5 days. Lower SIG levels correlated with better neurologic outcome. The highest correlation coefficient (0.63) was in the “no cooling” subcohort between diffusion-weighted scores and SIG levels at 24 hours; the latter also had the highest area under the receiver operating characteristic curve (AUC), 0.90, with positive and negative predictive values of 84 and 90%. SIG outperformed lactate in the “no cooling” subcohort, and vice-versa in the “cooling” subcohort. All BE AUCs were <0.6. Overall, the SIG is similar to lactate as a prognostic parameter. BE levels at 4, 24, and 48 hours after birth do not predict neurologic outcome. While not displacing lactate the SIG is an additional prognostic parameter for newborns in the first 2 days after hypoxia-ischemia.
Keywords: acidosis; asphyxia neonatorum; cerebral palsy; hypoxia-ischemia; magnetic resonance imaging; strong ion gap